PENOLAKAN TERHADAP NARASI BESAR DALAM NOVEL NEGARA KELIMA KARYA E.S. ITO (TINJAUAN DEKONSTRUKSI JACQUES DERRIDA) - Nurwahidin NL; Muhammad Rapi; Hajrah Hajrah (Universitas Negeri Makassar, 2016)
Abstract. “The rejection on Big narration in Negara kelima’ s novel by E.S. Ito (Jacques Derrida’s deconstruction analysis)”. The aim of this research is to describe the rejection of big naration text in Negara Kelima novel by E.S. Ito by using Jacques Derrida’s deconstruction analysis. This research is descriptive qualitative research. The source of the data is the Negara Kelima novel by E.S. Ito which is published by Serambi Ilmu Semesta. Then, the data is gained from the text in Negara Kelima novel by E.S. Ito which is a rejection on Big Narration according to Jacquess Derrida. The instrument of the research is self-research under the idea and knowledge about research by using Library research, the researcher understand, identify, analyze, then, describe based on the deconstruction theory from Jacques Derrida. The result of the research shows to us that E.S. Ito conducted a rejection on three big narration, the first one about science narration in terms of reading maps (Cartograf), in reading modern map, decosntruction allow the reader to do reverse reading in finding Ancient history. The second is about Religion narration (Islam), E.S Ito deconstruct the moeslem’s society paradigm about the existence of heaven, and the third is about history narration.